Computational modeling for rational design of novel phenoxy tacrine derivatives targeting Alzheimer’s disease - Mohamed El Fadili; Mohammed Er-rajy; Somdutt Mujwar; Abdelouahid Samadi; Samir Chtita; Menana Elhallaoui (PLoS ONE, 2026)
Alzheimer’s is the leading factor behind dementia, producing steady impairments in memory, cognitive reasoning, behavioral, and social interactions. This scientific study investigates thirty-two phenoxy tacrine (PhO-THA) derivatives through an integrated computational modeling to identify potential therapeutic candidates. 3D-QSAR models were developed using comparative molecular similarity indices analysis and comparative molecular field analysis, which were subjected to rigorous internal and external validation to establish a robust quantitative relationship between molecular interaction fields and cytotoxic activities. Based on these validated structural insights, fourteen new compounds (D1-D14) were designed. Comprehensive molecular docking and molecular dynamics (MD) simulations, coupled with ADME-Tox profiling, were used to evaluate their pharmacological potential. Our results highlight four specific compounds (D9-D12) that exhibit favorable pharmacokinetic properties and a high safety profile, making them promising candidates for future drug development. D9 was selected for MD simulations due to its lower cytotoxic activity (pIC 50 of 3.50), which is comparable to the reference THA drug (pIC 50 of 3.52). The results demonstrated exceptional thermodynamic stability for D9 upon complexation with the NMDA receptor (PDB ID: 5EWJ) over a 100 ns simulation time.